Electrochemical Storage: Catechol‐Mediated Reversible Binding of Multivalent Cations in Eumelanin Half‐Cells (Adv. Mater. 38/2014). (October 2014) - Kim, Young Jo; Wu, Wei; Chun, Sang‐Eun; Whitacre, Jay F.; Bettinger, Christopher J.
<x xml:space="preserve">Abstract</x> Biologically derived polymers from the cuttlefish can be leveraged as sustainable energy‐storage materials. Melanin pigments exhibit redox‐active chemistries and homogeneous nanostructured particles. Catechols can be oxidized into ortho‐quinones and reversibly bind magnesium cations with differential affinity as described by J. F. Whitacre, C. J. Bettinger, and co‐workers on page 6572. These properties of melanin biopolymers are advantageous for the potential use as cathodes in rechargeable magnesium ion batteries with high cycle stability. Photo credit: Brent Polishak. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>